2024
DOI: 10.1038/s41598-024-57049-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seed priming with Selenium nanoparticles on germination and seedlings growth of tomato

Ezequiel García-Locascio,
Edgardo I. Valenzuela,
Pabel Cervantes-Avilés

Abstract: Poor germination and seedlings growth can lead to significant economic losses for farmers, therefore, sustainable agricultural strategies to improve germination and early growth of crops are urgently needed. The objective of this work was to evaluate selenium nanoparticles (Se NPs) as nanopriming agents for tomato (Solanum lycopersicum) seeds germinated without stress conditions in both trays and Petri dishes. Germination quality, seedlings growth, synergism-antagonism of Se with other elements, and fate of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This is consistent with reports that selenium both promotes plant growth and enhances photosynthesis. For instance, García-Locascio et al found that the application of Nano-Se increased the contents of photosynthetic pigments in red kidney bean leaves and promoted vegetative growth . Similarly, Li et al showed that the application of Nano-Se to capsicum leaves increased the photosynthetic pigment content in the fruit, enhancing the fruit quality .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with reports that selenium both promotes plant growth and enhances photosynthesis. For instance, García-Locascio et al found that the application of Nano-Se increased the contents of photosynthetic pigments in red kidney bean leaves and promoted vegetative growth . Similarly, Li et al showed that the application of Nano-Se to capsicum leaves increased the photosynthetic pigment content in the fruit, enhancing the fruit quality .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Garci ́a-Locascio et al found that the application of Nano-Se increased the contents of photosynthetic pigments in red kidney bean leaves and promoted vegetative growth. 31 Similarly, Li et al showed that the application of Nano-Se to capsicum leaves increased the photosynthetic pigment content in the fruit, enhancing the fruit quality. 32 The chlorophyll fluorescence imaging system was used to show the fluorescence status of the four treatments, as shown in Figure 1F, and the corresponding Fv/Fm results are shown in Figure 1G.…”
Section: Effects Of Single Andmentioning
confidence: 97%